2012
DOI: 10.1103/physreve.86.011133
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic resonance in multistable systems: The role of dimensionality

Abstract: The theory of stochastic resonance in multistable systems is extended to account for both direct transitions between all stable states present and indirect ones involving intermediate states. It is shown that to satisfy these requirements the dynamics needs to be embedded in phase spaces of dimension equal to at least two. Under well defined conditions, the conjunction of the presence of intermediate states and the multidimensional character of the process leads to an enhancement of the response of the system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…We set out to obtain a pair of integro-differential equations which describes the equations of slow oscillations and the fast vibrations. The superposition of their solutions completely solves the PDM system given by in equation (22). Therefore we assume x y z.…”
Section: Theoretical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We set out to obtain a pair of integro-differential equations which describes the equations of slow oscillations and the fast vibrations. The superposition of their solutions completely solves the PDM system given by in equation (22). Therefore we assume x y z.…”
Section: Theoretical Analysismentioning
confidence: 99%
“…The occurrence of multiple attractors is often determined by the system class such as dissipation strength, coupling type and intensity, time delay, amplitude and frequency of parameter perturbation, nature of external forcing and noise intensity [17,19]. These system components have been shown to influence several nonlinear phenomena observed in multistable systems including synchronization, memory capability mechanism in artificial neural networks, absolute negative mobility and current reversal, hidden and selfexcited attractors, chaos and nonlinear resonance [20][21][22][23][24]. A much studied type of nonlinear resonance observed in multistable systems with weak signal generated by applying white noise to an external signal with a broad frequency range is the stochastic resonance (SR) [25].…”
Section: Introductionmentioning
confidence: 99%
“…We shall argue in this and the following sections that the higher catastrophe that organizes the BH trimer dynamics is in fact the high order umbilic catastrophe known by its group-theoretic symbol, X 9 . This complicated object has previously been the subject of detailed theoretical analysis by Borghi [186] and by Berry and Howls [187], and plays an important role in optical refraction through twodimensional surfaces, such as water droplets [188], glass junctions [189], gravitational lensing [92], and has also been discussed in the context of stochastic resonance in two dimensions [190]. X 9 acts as an organizing centre for a multitude of lower catastrophes and we refer the reader to Fig.…”
Section: The X9 Catastrophementioning
confidence: 99%
“…At present, most research achievements of stochastic resonance were based on the one-dimensional potential system, while the two-dimensional potential system lacks sufficient research due to the coupling of system state variables and the complexity of inter-well transitions. Nicolis (2012) and Nicolis and Nicolis (2017) extended the inter-well dynamics of a multi-stable system to a two-dimensional space and found that the synergistic effect of intermediate steady-state and multidimensional characteristics would enhance the system response. Therefore, the SR mechanism of the one-dimensional and two-dimensional potential systems is very worthy of attention and research.…”
Section: Introductionmentioning
confidence: 99%